House of cards. The complete first season - Fincher, David; Spacey, Kevin; Wright, Robin, 1966-; Kelly, Michael, 1969-; Dobbs, Michael, 1948- (Culver City, Calif. : Sony Pictures Home Entertainment, 2013)
Ruthless congressman Francis Underwood trades secrets for political access with an ambitious journalist in his quest to become the next president of the United States.
Based on the novels by Michael Dobbs.
Kevin Spacey, Robin Wright, Michael Kelly, Kristen Connolly, Kate Mara, Corey Stoll.
TV rating: Not rated.
DVDs, Dolby digital 5.1.
In English with optional English, French, Portuguese, or Spanish subtitles.
Closed-captioned.
Keywords: Dobbs, Michael, -- 1948- -- Television adaptations; Politicians -- Washington (D.C.) -- Drama; Journalists -- Washington (D.C.) -- Drama; Political corruption -- Washington (D.C.) -- Drama; Washington (D.C.) -- Drama; Political television programs; Television series; Fiction television programs; Video recordings for the hearing impaired; Based on the book